Effectiveness of a school-based fire preparedness program on the knowledge and skills for fire response among primary school students - Anchalee Katramee; Weerapong Thanjangreed (International Journal of Occupational Safety and Health, 2025)
Introduction: In the border region of Thailand, the absence of a standardized school preparedness program exposes schools to the risk of fires, which can result in injuries, fatalities, and property damage. This study aims to assess the effectiveness of a fire preparedness program for primary schools in Chiang Rai province's border area, serving students from various ethnic backgrounds.